Looking at the big picture in activation strain model/energy decomposition analysis: The case of the: Ortho - Para regioselectivity rule in Diels-Alder reactions - Grimblat, Nicolas (2020)
The regioselectivity of the Diels-Alder reaction is predicted by the ortho-para rule which has been explained from FMO theory. Using DFT calculations, the activation-strain model and energy decomposition analysis we studied the reaction of methyl acrylate with four unsymmetrical dienes. We found that if the analysis is carried out considering the TS structures, the selectivity would not be explained by the interaction energy as expected considering the FMO arguments. However, a thorough analysis along the reaction path revealed that the interaction energy is responsible for the regioselectivity. A deeper analysis with the EDA model showed that the decisive term that accounts for the HOMO-LUMO interactions favors the ortho and para paths, as predicted by FMO arguments.